Secondary electron emission induced by α-particles from Mg-MgO layers - Zhurenko, V.P.; Kononenko, S.I.; Mahotka, I.S.; Kalantaryan, O.V.; Mysiura, I.M.; Avotin, S.S.; Rokhmanov, N.Ya. (Вопросы атомной науки и техники, 2019)
The paper presents the results of experimental study of forward and backward electron emission induced by α- particles from the deposited film of magnesium. It was shown that during the deposition of magnesium in residual gas atmosphere the deposited film contained a large amount of MgO component, which makes it possible to consider the resulting structure as Mg-MgO. The presence of magnesium oxide on the surface of the target and the collector leads to the fact that the previously obtained dependence of the ratio of forward and backward electron yields on specific energy loss of the ion for various metals is not applicable in the case of deposited magnesium. The differences are explained by the specificity of the emission from magnesium in the presence of a significant amount of MgO. The results obtained can be used to detect MgO on the surface of a magnesium substrate. It was shown the differences in the experimental data for the bulk magnesium collector and the collector with deposited magnesium layer. Наведено результати експериментів з дослідження емісії електронів, що індукована α-частинками на простріл і на відбиття з напилених плівок магнію. Було показано, що в разі напилення магнію в атмосфері залишкового газу утворена плівка містить велику кількість компонента MgO, що дозволяє розглядати отриману структуру як Mg-MgO. Наявність окису магнію на поверхні мішені та колектора призводить до того, що отримана раніше залежність відносин електронних виходів на простріл і на відбиття від питомих втрат енергії іона для різних металів не може бути застосована в разі напиленого магнію. Отримані відмінності пояснюються специфікою емісії з магнію за наявності значної кількості MgO. Отримані результати можуть бути застосовані для детектування MgO на поверхні магнієвого субстрату. Було показано і пояснено відмінності в експериментальних даних для масивного магнієвого колектора і колектора з напиленим шаром магнію. Приведены результаты экспериментов по исследованию эмиссии электронов, индуцированной α-частицами на прострел и на отражение из напыленной пленки магния. Было показано, что при напылении магния в атмосфере остаточного газа пленка содержит большое количество компонента MgO, что позволяет рассматривать полученную структуру как Mg-MgO. Наличие окиси магния на поверхности мишени и коллектора приводит к тому, что полученная ранее зависимость отношений электронных выходов на прострел и на отражение от удельных потерь энергии иона для различных металлов не применима в случае напыленного магния. Полученные различия объясняются спецификой эмиссии из магния при наличии значительного количества MgO. Полученные результаты могут быть применены для детектирования MgO на поверхности магниевого субстрата. Были показаны и объяснены различия в экспериментальных данных для массивного магниевого коллектора и коллектора с напыленным слоем магния.